Ask Question
11 January, 23:40

3 (t+4) - 2 (2t+3) solve for t

+3
Answers (1)
  1. 12 January, 01:43
    0
    t=3

    Step-by-step explanation:

    ((3 * (t+4)) - 2 * (2t+3)) - t=0

    (3 • (t + 4) - 2 • (2t + 3)) - t = 0

    6 - 2t = - 2 • (t - 3

    -2 • (t - 3) = 0

    t-3 = 0

    t=3
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “3 (t+4) - 2 (2t+3) solve for t ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers